2017
DOI: 10.1136/gutjnl-2016-313332
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial profile is altered in primary biliary cholangitis and partially restored after UDCA therapy

Abstract: This study presents a comprehensive landscape of gut microbiota in PBC. Dysbiosis was found in the gut microbiome in PBC and partially relieved by UDCA. Our study suggests that gut microbiota is a potential therapeutic target and diagnostic biomarker for PBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
332
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(350 citation statements)
references
References 44 publications
9
332
2
7
Order By: Relevance
“…In their study, Lv et al observed that early stage PBC patients had reductions of several potentially beneficial gut microbiota (such as Acidobacteria, Lachnobacterium sp, etc), and the enrichment of some opportunistic pathogens (such as γ‐Proteobacteria, Enterobacteriaceae, etc) . Tang and co‐workers observed reduced species richness and a lower level of microbial diversity in patients with PBC and partial restoration of these changes after UDCA treatment . However, these investigators did not report gut microbiota in relation to pruritus associated with PBC.…”
Section: Discussionmentioning
confidence: 96%
“…In their study, Lv et al observed that early stage PBC patients had reductions of several potentially beneficial gut microbiota (such as Acidobacteria, Lachnobacterium sp, etc), and the enrichment of some opportunistic pathogens (such as γ‐Proteobacteria, Enterobacteriaceae, etc) . Tang and co‐workers observed reduced species richness and a lower level of microbial diversity in patients with PBC and partial restoration of these changes after UDCA treatment . However, these investigators did not report gut microbiota in relation to pruritus associated with PBC.…”
Section: Discussionmentioning
confidence: 96%
“…26 Individual variation in Gammaproteobacteria has been directly linked with susceptibility to fatty liver disease. 12,30 This indicates that these alterations might be rather unspecific features of chronic liver disease. 28,29 For eight taxa across different taxonomic levels we demonstrated a consistently increased abundance in patients with PSC.…”
Section: Diet Has Minor Impact On Microbial Community Alterations Imentioning
confidence: 99%
“…Both genera comprise butyrate-producing species, which provide an important energy source for intestinal epithelia and display an array of beneficial immunological properties 33. This finding further underlines its potential importance for the understanding of the pathophysiology and development of novel therapeutic approaches in inflammatory intestinal and liver diseases, where depletion of Faecalibacterium is a frequently observed common trait 11,30. This finding further underlines its potential importance for the understanding of the pathophysiology and development of novel therapeutic approaches in inflammatory intestinal and liver diseases, where depletion of Faecalibacterium is a frequently observed common trait 11,30.…”
mentioning
confidence: 96%
“…In a recent study, a reduction in several potentially beneficial microbes and an enrichment in several opportunistic pathogens was observed in the GM of early‐stage PBC patients . Another paper reported that an observed reduction in species richness and a significant shift in the overall microbial diversity in PBC patients could be partially ameliorated after ursodeoxycholic acid (UDCA) treatment . Taken together, it is clear that the GM is directly involved in the pathogenesis of autoimmune cholestatic liver diseases.…”
Section: Gut Microbiome and Bas In Liver Diseasesmentioning
confidence: 96%
“…104 Another paper reported that an observed reduction in species richness and a significant shift in the overall microbial diversity in PBC patients could be partially ameliorated after ursodeoxycholic acid (UDCA) treatment. 105 Taken together, it is clear that the GM is directly involved in the pathogenesis of autoimmune cholestatic liver diseases. Targeting this cross-talk between BAs and GM could offer exciting new perspectives for the treatment of cholestatic liver diseases like PSC and PBC.…”
Section: Autoimmune Liver Diseasesmentioning
confidence: 99%